AWARENESS ABOUT MEDICAL APPLICATIONS OF QL-47 AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
QL47, a Bruton tyrosine kinase inhibitor, is a host-targeted, small-molecule antiviral that inhibits steady-state viral protein expression. This small molecule broadly inhibits both viral and host protein synthesis and targets a translation step specific to eukaryotic cells and has the potential to be used as antiviral medication. The aim of the study was to assess the awareness about medical applications of QL-47 among dental students. This was a questionnaire-based cross-sectional type of study comprising 100 dental college students in Chennai. A self-designed questionnaire with 10 questions eliciting the knowledge and awareness about QL 47 therapy among dental college students. Questionnaires were circulated through an online website survey planet The questions explored the awareness of QL 47 therapy, indications, contraindications, mechanism of action, and side effects. After the responses were received from 100 participants, data was collected and analyzed. 5% were aware of QL 47 therapy. 3% were aware of the mechanism of action of QL 47 therapy. 4% were aware of the indications of QL 47 therapy. 3% were aware of the QL 47 therapy. 3% were aware of the side effects of QL 47 therapy . The awareness about QL 47 in medical applications and managing viral infections was less among dental students. Increased awareness and educational programs should be initiated to spread knowledge about QL 47 therapy.